Modeling blood pressure using windkessel model - Wang, Chutong (2019)
Healthcare is a fast-growing industry now catering to the increasing demand of people. Blood pressure is an essential parameter for health condition evaluation. Non-invasive and continuous methods for blood pressure measurement support patients to do monitoring in home and hospital. Among them, Windkessel model is one of the advanced methods used in blood pressure measurement and 2-element Windkessel model has been widely used in the literature. In this dissertation, we work on analyzing and testing few Windkessel models and attempt to develop a more sensitive and accurate Windkessel model. Experimental results that are performed on a standard hospital dataset yield few errors for blood pressure estimation using the basic 2-element Windkessel model. The simulated plots also show the loss of some detailed information. Using the modified Windkessel model, additional features like dicrotic notch can be clearly shown in the simulated signal but with an increase in computational complexity.